Assessment of performance, physiological responses, and movement technique in cross-country skiing using sensor data - Seeberg, T. M. (Norwegian University of Science and Technology (NTNU), 2023)
The main objective of this thesis was to investigate physiological responses, movement techniques, and their associations with training intensity and performance in cross-country skiing (XC) using sensor data, with a particular emphasis on mass-start competitions and the skating technique. The thesis followed a sequential approach, starting with two indoor studies conducted under standardized conditions. In these studies (Paper 1 and Paper 2), wearable sensors were used in conjunction with standard laboratory measurements to establish a foundation for interpreting data collected from sensors in outdoor settings. This approach allowed for the integration of highly accurate reference sensors and methodology, contributing to the development of expertise in analyzing outdoor sensor data.